2002
DOI: 10.1046/j.1396-5883.2001.02373.x
|View full text |Cite
|
Sign up to set email alerts
|

Computer literacy and attitudes among students in 16 European dental schools: current aspects, regional differences and future trends

Abstract: A questionnaire survey was carried out to investigate the competence and attitude of dental students towards computers. The current study presents the findings deriving from 590 questionnaires collected from 16 European dental schools from 9 countries between October 1998 and October 1999. The results suggest that 60% of students use computers for their education, while 72% have access to the Internet. The overall figures, however, disguise major differences between the various universities. Students in Northe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
49
0
1

Year Published

2004
2004
2014
2014

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(56 citation statements)
references
References 12 publications
6
49
0
1
Order By: Relevance
“…Similar were the recommendations by Malaysian study [10] which suggested formal inclusion of ICT instruction in the teaching of undergraduate medicine, to enhance medical students' ability to acquire, appraise, and use information to solve clinical and other problems. A comparative analysis of the past studies and the present study is depicted in [Table/ Fig-10].…”
Section: Discussionsupporting
confidence: 63%
See 1 more Smart Citation
“…Similar were the recommendations by Malaysian study [10] which suggested formal inclusion of ICT instruction in the teaching of undergraduate medicine, to enhance medical students' ability to acquire, appraise, and use information to solve clinical and other problems. A comparative analysis of the past studies and the present study is depicted in [Table/ Fig-10].…”
Section: Discussionsupporting
confidence: 63%
“…Studies depict high utilization patterns of ICT among health care professionals and learners [8]. In contrast to its extensively acknowledged importance; computer access and computer related skills demonstrate a wide diversity, both regional and within students and faculties of the same institution [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] This study surveyed the current knowledge and skills of dental students at Riyadh Colleges of Dentistry and Pharmacy (RCSDP) in use of information and communications technology (ICT). Analyzing IT skills is especially difficult when comparing results over a span of years: what would be seen as a trivial computer task today may have required advanced knowledge a few years ago.…”
Section: Discussionmentioning
confidence: 99%
“…To conduct the study, we used a questionnaire derived from previous surveys. [5][6][7] The questionnaire (questions and results are shown in Tables 1-4 in appendixhttp://www.jdentaled.org/cgi/ content/full/69/3/387 -T6) consisted of thirty three multiple choice questions in English language (with only questions translated in Arabic). The questionnaire was circulated among the other faculty to obtain comments on its applicability.…”
Section: Methodsmentioning
confidence: 99%
“…1 Information and communication technology (ICT) is currently used in many areas of oral health care, including electronic databases, data transfer and practice management. 2 Appropriate ICT tools (such as email, online databases, internet and computer-assisted learning) may be utilised by staff, not only for personal and professional development, but also for the benefit of patients. 3 There is a national agenda for the development of ICT within health care 4 and firm warnings have been issued about the dangers of 'being left behind'.…”
Section: Introductionmentioning
confidence: 99%